Childhood Hypopigmented Mycosis Fungoides: A Rare Diagnosis - Cláudia Patraquim; Maria Miguel Gomes; Carla Garcez; Filipa Leite; Tereza Oliva; António Santos; Armando Pinto (Case Reports in Pediatrics)
Primary cutaneous lymphomas (PCL) are rare in pediatrics. Mycosis fungoides (MF) is the most frequent PCL diagnosed in childhood. There are various clinical variants of MF, including the hypopigmented MF (HMF). We present a 5-year-old boy with an 18-month history of progressive, generalized, nonpruritic hypopigmented lesions with central lacy erythema. He had no improvement with emollients. Skin biopsy showed typical features of HMF. He was treated with topical corticosteroids and tacrolimus and narrow-band ultraviolet B (NBUVB) phototherapy, with good response. HMF may mimic multiple skin disorders. Unusual hypopigmented skin lesions should be biopsied. Though phototherapy is effective, recurrence is common.